Petrogenesis of fractionated nested granite intrusions: the Sedmihori Composite Stock (Bohemian Massif) - Trubac,J.; Janousek,V.; Gerdes,A. (Journal of Geosciences, 2019)
The post-tectonic Sedmihori Stock (SCS) is a circular body in plan-view, made up of three nested units: (i) ’Outer granite’ (OG), less fractionated Kfs-phyric Bt monzogranite (326.2 ± 1.2 Ma (2σ), LA ICP-MS Zrn), (ii) ’Inner granite’ (IG), more evolved Bt-Ms monzogranite (326.6 ± 1.2 Ma), and (iii) innermost leucogranite (’LG’), fine-grained Tur-Ms leucogranite.All the varieties of this body are silica-rich (SiO2 > 71 wt. %) and subaluminous to strongly peraluminous (A/CNK = 1.01-1.25). Major-element contents do not vary greatly but the trace elements show more significant differences between the granite varieties. From OG to LG, the rocks show decreasing overall REE abundances and La/Yb ratios.Significant differences in Th and U concentrations occur between the marginal OG (˜49 ppm Th; ˜9 ppm U) and the more central IG (˜8 ppm Th, ˜4 ppm U). Hydrothermal thorite (recorded in the OG), xenotime and monazite are the main accessories concentrating these radioactive elements. The final stage of the magma evolution is represented by the central LG pulse containing beryl, wolframite and high-Li muscovite.All pulses of the SCS are characterized by crust-like Sr-Nd isotopic signatures. The inner IG shows more evolved Sr (87Sr/86Sr326 = 0.7098-0.7130) and less radiogenic Nd (εNd326 = -4.6 to -3.7) than the outer OG (87Sr/86Sr326 = 0.7067-0.7076; εNd326 = -2.5 to -2.7).The granite batches were probably derived by anatexis of Neoproterozoic or, more likely, Cambrian metagreywackes of the Tepla-Barrandian Unit. Enriched-mantle derived magmas (redwitzites) played a very important role that not only provided the heat needed for the anatexis, but also variably contributed material via magma mixing processes. The hybridization was particularly significant for the origin of the outer unit, which is rich in mafic microgranular enclaves and whose Sr is the least and Nd most radiogenic within the SCS.Taken together, field observations, structural relations, U-Pb zircon dating and geochemistry indicate that all pulses in the SCS were emplaced nearly simultaneously. However, each of them represented a single batch of magma with its own geochemical characteristics and petrogenetic features.
Keywords: nested pluton; highly fractionated granite; petrology; geochemistry; Tepla-Barrandian; Bohemian Massif